2019
DOI: 10.1007/s00268-019-05191-9
|View full text |Cite
|
Sign up to set email alerts
|

Is Preoperative Fibrinogen Associated with the Survival Prognosis of Gastric Cancer Patients? A Multi‐centered, Propensity Score‐Matched Retrospective Study

Abstract: Background The prognostic significance of preoperative plasma fibrinogen in patients with operable gastric cancer remains under debate. This study aimed to elucidate the prognostic value of fibrinogen in gastric cancer patients underwent gastrectomy. Methods A total of 4351 patients with gastric cancer collected from three comprehensive medical centers were retrospectively evaluated. Patients were categorized by minimum P value using X-tile, while the baseline confounders for fibrinogen was balanced through pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…FIB is the main coagulation factor in plasma, and its normal concentration is about 2 to 4 g/L [7]. A high level of plasma FIB in patients with lung cancer, ESCC, gastric cancer, colorectal cancer, ovarian cancer, and other cancers is independently associated with poor prognosis [8][9][10][11]. A reduced FIB level occurs in disseminated intravascular coagulation (DIC), severe hepatitis, cirrhosis, thrombolytic therapy, primary brinolysis, and several other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…FIB is the main coagulation factor in plasma, and its normal concentration is about 2 to 4 g/L [7]. A high level of plasma FIB in patients with lung cancer, ESCC, gastric cancer, colorectal cancer, ovarian cancer, and other cancers is independently associated with poor prognosis [8][9][10][11]. A reduced FIB level occurs in disseminated intravascular coagulation (DIC), severe hepatitis, cirrhosis, thrombolytic therapy, primary brinolysis, and several other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally regarded as a key factor of coagulation and brinolytic activation. Recently, A lot of research shows that an elevated pre-treatment plasma Fib level is closely associated with poor prognosis in patients with various malignant tumours [18][19][20][21], including breast cancer [12][13][14]. In a large retrospective study of 2073 consecutive breast cancer patients, Wen et al [12] reported that an elevated preoperative plasma Fib level was an independent prognostic factor for overall survival in breast cancer patients who underwent surgical treatment (p=0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Most patients (91.4%) received 4 chemotherapy cycles, and ductal (96.7%) was the most frequent histological subtype. The subtype distribution was as follows: 35.9% for HR (+) HER2 (-), 21.0% for HR (+) HER2 (+), 21.5% for HR (-) HER2 (+), 15.5% for HR (-) HER2 (-), and 6.1% for unknown. A total of 128 patients (12.4%) achieved pCR to NAC.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…To reduce the impact of potential confounding factors and effects of selection bias such as baseline clinicopathologic factors or uneven patient distribution between the CA19-9 changing more than 20% and no more than 20%, 1:1 propensity score matching (PSM) was applied to adjust for age, tumor size, macroscopic type, histological grade, and T stage and TNM stage. A 0.2-width caliper of the standard deviation of the logit was applied to match across the two groups ( 18 , 19 ). P -values less than 0.05 were considered significant.…”
Section: Methodsmentioning
confidence: 99%